The sublime in hate propaganda on the Internet - a critical discourse analysis - Rinn, Michael (Redis: Revista de Estudos do Discurso, 2019)
This paper considers how two rhetorical concepts, pathos and the sublime, are used to reinforce hate propaganda on radical Islamist websites. The concept of pathos comes from Aristotle’s theory on modes of persuasion, which is based on the idea of stimulating dialogue, debate or even argument between a speaker and an audience to bring about the most favourable choice for the common good. The raison d’être of rhetoric, namely negotiation of social meaning through persuasive speech, has been recognised since Greek Antiquity. Although the desired goal of hate propaganda, above all else, is the destruction of social life, this article will show why pathos can be used to establish inter-subjectivity in a pseudo-shared social space, strengthening the impact of its persuasive action. Unlike pathos, the sublime is a sophist concept. Analysis of Islamic State’s website (jihadology.net) reveals how the sublime is used to trigger action influenced by constraint, fear and intense violence, through language. Hate propaganda uses the sublime as a tool for radical manipulation. The article will show how this strategy not only deprives Internet users of all ability to judge, but also transforms them into agents totally committed to the destruction of society.